Then and now: lessons learned from community- academic partnerships in environmental health research - Lichtveld, Maureen (Environ Health, 2016)
On the occasion of the 50(th) anniversary of the National Institutes of Environmental Health Sciences we reflect on how environmental research incorporating community members as active partners has evolved, benefited communities and advanced environmental health research. We highlight the commitment to community partnerships in the aftermath of the 2010 Deep Water Horizon Oil Spill, and how that commitment helped improve science. We provide examples of community-academic partnerships across the engagement spectrum. Finally, we offer suggestions to improve the community engagement in order to cultivate more long partnerships and better scientific research.